2014
DOI: 10.1002/rcs.1584
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the biomechanical effects of pertrochanteric fixator and dynamic hip screw on an intertrochanteric femoral fracture using the finite element method

Abstract: This study demonstrated that PTF is more favorable than DHS for early axial loading and ambulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Moreover, in China, 70% of surgeons prefer PFNA over DHS for treating a stable intertrochanteric fracture in active elderly patients [10]. Other studies have previously reported that DHS was the best choice for the initial treatment of stable intertrochanteric fractures [6, 7, 9, 16, 17]. Although the complication rates of DHS devices ranged from 12 to 34% [10], DHS was still regarded as a preferred device for stable intertrochanteric fractures in active elderly patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in China, 70% of surgeons prefer PFNA over DHS for treating a stable intertrochanteric fracture in active elderly patients [10]. Other studies have previously reported that DHS was the best choice for the initial treatment of stable intertrochanteric fractures [6, 7, 9, 16, 17]. Although the complication rates of DHS devices ranged from 12 to 34% [10], DHS was still regarded as a preferred device for stable intertrochanteric fractures in active elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no consensus about which type of implant to use or what technique to perform in patients with stable intertrochanteric fractures previously treated with DHS fixation or PFNA. Some studies reported no difference in the clinical and radiological outcomes [712, 19, 20], while others reported higher complication rates and revision rates for one approach after CTHA [17, 21]. To address this controversy, we compared the clinical and radiological outcomes of CTHA after a failed PFNA or DHS fixation for stable intertrochanteric fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a major treatment for intertrochanteric fractures. [12][13][14][15] The proximal end and binding position of the plate have strong bending resistance so create strong fixation, better sliding function. It also has static and dynamic characteristics of pressurizing action and applies pressure on fracture ends.…”
Section: Discussionmentioning
confidence: 99%
“…It is also used as a reliable technique for validation of experimental or analytical results. In addition, several scientists similarly examined the optimal configuration, implant materials, fatigue behavior of implant materials, metal turning, bone drilling and bone screwing process using the computer aided FEA tool [18][19][20][21][22][23][24].…”
Section: Computer Aided Finite Elementmentioning
confidence: 99%